In-vitro Anti-Plasmodial Activity of Mangifera indica Leaves Against Plasmodium falciparum - R. H., Muhammad; F. S., Sunusi; M., Safiyanu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Malaria remains a critical global health concern, particularly in sub-Saharan Africa, where Plasmodium falciparum accounts for the majority of infections and fatalities. With increasing resistance to the current antimalarial treatments, including artemisinin-based combination therapies (ACTs), there is growing interest in exploring natural remedies, especially plant-derived alternatives. The current study investigated the in-vitro antiplasmodial activity of aqueous leaf extracts of Mangifera indica (mango). Phytochemical evaluation of the leaf extract revealed the presence of flavonoids, tannins, saponins, and terpenoids, compounds with known pharmacological relevance. The extract showed a reduction in parasitemia in the culture based on different concentrations, achieving a maximum inhibition rate of 93% at 10 mg/ml, comparable to that of the artemether control (96%). The study's findings revealed that M. indica leaf extract holds promise as an affordable and effective candidate for the development of antimalarial drugs. Further investigations should focus on isolating specific active compounds, elucidating their mechanisms of action, and conducting in vivo validation studies, which are highly recommended.